Artificial Intelligence and Health Care for Older Adults, a Future for All of Us - Peter M. Abadir; Phillip H. Phan; Márlon Juliano Romero Aliberti; Thiago Junqueira Avelino‐Silva; Caglar Cosarderelioglu; April Ehrlich; Thomas Horton; Thomas Laskow; Sohemi Pagan Leon; Sarah Lenz Lock; Mark A. Supiano; Daniel Thomas; et al. (Journal of the American Geriatrics Society, 2026)
ABSTRACT We are racing towards a time wherein the largest demographic of the population will be comprised of older adults and where it is now also possible to measure, monitor, and diagnose long term risk factors and provide effective and valuable preventative interventions. Thanks to the achievements of modern health care, we have reached a tipping point in the need for a robust geriatric workforce. Through the implementation of thoughtful, deliberate, and collaborative processes, Artificial Intelligence can play a significant role in preparing individuals in both mind and body for healthy aging. On May 1, 2025, the Johns Hopkins Artificial Intelligence and Technology Collaboratory (JH AITC) hosted a one‐day summit in Washington, DC, to explore the future and potential uses of Artificial Intelligence (AI) for older adults. Presenters and participants discussed the challenges facing the implementation of this technology into the U.S. health care system and the opportunities recent advances are affording in improving the quality of life for older adults.